Effects of pulsed atrazine exposures on autotrophic community structure, biomass, and production in field‐based stream mesocosms. (25th January 2016) - King, Ryan S.; Brain, Richard A.; Back, Jeffrey A.; Becker, Christopher; Wright, Moncie V.; Toteu Djomte, Valerie; Scott, W. Casan; Virgil, Steven R.; Brooks, Bryan W.; Hosmer, Alan J.; Chambliss, C. Kevin
Abstract: The authors performed a multiple‐pulsed atrazine experiment to measure responses of autotrophic endpoints in outdoor stream mesocosms. The experiment was designed to synthetically simulate worst‐case atrazine chemographs from streams in agricultural catchments to achieve 60‐d mean concentrations of 0 μg/L (control), 10 μg/L, 20 μg/L, and 30 μg/L. The authors dosed triplicate streams with pulses of 0 μg/L, 50 μg/L, 100 μg/L, and 150 μg/L atrazine for 4 d, followed by 7 d without dosing. This 11‐d cycle occurred 3 times, followed by a recovery (untreated) period from day 34 to day 60. Mean ± standard error 60‐d atrazine concentrations were 0.07 ± 0.03 μg/L, 10.7 ± 0.05 μg/L, 20.9 ± 0.24 μg/L, and 31.0 ± 0.17 μg/L for the control, 10‐μg/L, 20‐μg/L, and 30‐μg/L treatments, respectively. Multivariate analyses revealed that periphyton and phytoplankton community structure did not differ among treatments on any day of the experiment, including during the atrazine pulses. Control periphyton biomass in riffles was higher immediately following the peak of the first atrazine pulse and remained slightly higher than some of the atrazine treatments on most days through the peak of the last pulse. However, periphyton biomass was not different among treatments at the end of the present study. Phytoplankton biomass was not affected by atrazine. Metaphyton biomass in pools was higher in the controls near the midpoint of the present study and remained higher on most days for the remainder of the study. Ceratophyllum demersum, a submersed macrophyte, biomass was higher in controls than in 20‐μg/L and 30‐μg/L treatments before pulse 3 but was not different subsequent to pulse 3 through the end of the present study. Maximum daily dissolved oxygen (DO, percentage of saturation) declined during each pulse in approximate proportion to magnitude of dose but rapidly converged among treatments after the third pulse. However, DO increased in controls relative to all atrazine treatments during the last 17 d of the experiment, likely a result of metaphyton cover in the pools. Finally, atrazine significantly limited uptake of PO4 3– and uptake and/or denitrification of NO3 – but only during pulses; percentage of dose removed from the water column was >85% for P and >95% for N after pulse 3 through the end of the present study. Collectively, only DO and metaphyton biomass differed at the end of the present study and only slightly. Some other endpoints were affected but only during pulses, if at all. The high levels of primary production and accumulation of algal biomass in all streams suggest that effects of pulses of atrazine at the concentrations used in the present study appear transient and likely do not represent ecologically significant adverse outcomes to periphyton, phytoplankton, and aquatic macrophytes, particularly in agricultural streams subjected to high nutrient loads. Environ Toxicol Chem 2016;35:660–675. © 2015 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals, Inc. on behalf of SETAC.